2011
DOI: 10.1158/1078-0432.ccr-10-3069
|View full text |Cite
|
Sign up to set email alerts
|

Excellent Prognosis in a Subset of Patients with Ewing Sarcoma Identified at Diagnosis by CD56 Using Flow Cytometry

Abstract: Purpose: Ewing sarcoma (ES) is considered a systemic disease with the majority of patients harboring micrometastases at diagnosis. Multiparameter flow cytometry (MPFC) was used to detect ES cells in bone marrow (BM) of ES patients at diagnosis and to evaluate the prognostic significance of CD56 expression in BM samples.Experimental Design: BM samples from 46 ES patients, 6 tumor aspirates, 2 ES cell lines, and 10 control BM samples were analyzed by MPFC. ES cells were identified by the combination of CD45À/CD9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 43 publications
(63 reference statements)
1
19
1
Order By: Relevance
“…(2, 8, 13) Of particular interest, Ash and colleagues retrospectively analyzed 46 archival frozen BM samples from newly diagnosed ES patients (of which 35 BM samples were from patients with localized disease) using a similar multi-parametric flow cytometry method. They observed no significant differences in outcome and clinical parameters according to the level of occult BM involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2, 8, 13) Of particular interest, Ash and colleagues retrospectively analyzed 46 archival frozen BM samples from newly diagnosed ES patients (of which 35 BM samples were from patients with localized disease) using a similar multi-parametric flow cytometry method. They observed no significant differences in outcome and clinical parameters according to the level of occult BM involvement.…”
Section: Discussionmentioning
confidence: 99%
“…(3, 6) Other PCR-based studies have not confirmed this finding(2, 8), nor did a small retrospective study that utilized flow cytometry to quantify BM micrometastatic disease burden. (13) Beyond initial diagnosis, the persistence of PB and/or BM fusion transcripts after chemotherapy has been shown to confer an adverse prognosis. (2)…”
Section: Introductionmentioning
confidence: 99%
“…Roughly half of the patients with localized disease at diagnosis will relapse within 5 years or later after completing the extensive multimodal therapy [3]. Based on the aggressive clinical course and relatively low curative rate, it has been proposed that ES may be a systemic disease characterized by micrometastases at submicroscopic level [47]. …”
Section: Introductionmentioning
confidence: 99%
“…In our tumor, the CD99 remained positive only in the undifferentiated cells and not in ganglion cells. If CD56 is frequently expressed in NB [3], it could be found in ES and was associated in good prognosis [10]. In our case, the positivity of CD56 was only found in NB-like foci of the tumor.…”
Section: Discussionmentioning
confidence: 50%